Kids' perceptions on gaming experience and learning with the Nintendo Labo: Multiple “make” and “play” experiences - Cano, John; Chow, Megan (Revista Colombiana de Ciencias Sociales, 2024)
This paper explores the perceptions of kids that had the chance to explore the “Make” and “Play” phases of the Nintendo Labo variety “Toy-Con 01”. Focusing on the roles of engagement, knowledge utilization and acquisition of new concepts. This paper broadens the general understanding of how video games can elicit active learning. Building on the experiences in constructing DIY projects, the authors analyze how the kids —through four different cases— connected their previous knowledge and experiences with science-related content (implicit in the interactions and hardware of the Nintendo Switch console and the Nintendo Labo software and cardboard pieces). The results of the study show that kids can use their cultural and academic experiences as well as their funds of knowledge to make sense or create theories and hypotheses of how the hardware and the software of the Nintendo Labo interact with each other and work. The limitations of the study suggest that more time is needed to have a more in-depth exploration of the kids’ perceptions by exploring the “Discover” phase —the third and final phase of the Nintendo Labo.